Fulminant hepatitis and elevated levels of sIL-2R in thyroid storm. (27th September 2019) - Tanaka, Yuri; Uchida, Taisuke; Yamaguchi, Hideki; Kudo, Yohei; Yonekawa, Tadato; Nakazato, Masamitsu
Abstract : Summary: We report the case of a 48-year-old man with thyroid storm associated with fulminant hepatitis and elevated levels of soluble interleukin-2 receptor (sIL-2R). Fatigue, low-grade fever, shortness of breath, and weight loss developed over several months. The patient was admitted to the hospital because of tachycardia-induced heart failure and liver dysfunction. Graves' disease with heart failure was diagnosed. He was treated with methimazole, inorganic iodide, and a β-blocker. On the day after admission, he became unconscious with a high fever and was transferred to the intensive care unit. Cardiogenic shock with atrial flutter was treated with intra-aortic balloon pumping and cardioversion. Hyperthyroidism decreased over 10 days, but hepatic failure developed. He was diagnosed with thyroid storm accompanied by fulminant hepatitis. Laboratory investigations revealed elevated levels of sIL-2R (9770 U/mL). The fulminant hepatitis was refractory to plasma exchange and plasma filtration with dialysis, and no donors for liver transplantation were available. He died of hemoperitoneum and gastrointestinal hemorrhage due to fulminant hepatitis 62 days after admission. Elevated circulating levels of sIL-2R might be a marker of poor prognosis in thyroid storm with fulminant hepatitis. Learning points: The prognosis of thyroid storm when fulminant hepatitis occurs is poor. Liver transplantation is the preferred treatment for fulminant hepatitis induced by thyroid storm refractory to plasma exchange. Elevated levels of soluble interleukin-2 receptor might be a marker of poor prognosis in patients with thyroid storm.